2017
DOI: 10.1016/j.red.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Complex-task biased technological change and the labor market

Abstract: In this paper we study the relationship between task complexity and the occupational wageand employment structure. Complex tasks are defined as those requiring higher-order skills, such as the ability to abstract, solve problems, make decisions, or communicate effectively. We measure the task complexity of an occupation by performing Principal Component Analysis on a broad set of occupational descriptors in the Occupational Information Network (O*NET) data. We establish four main empirical facts for the U.S. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The highest value is observed for physicists and astronomers and the lowest for vehicle cleaners. As Caines, Hoffmann, and Kambourov (2017) show, this variable positively correlates with wage levels and growth, underlining the economic benefits of more complex occupations. We use the 2019 Standard Occupational Classification to International Standard Classification of Occupations (SOC-to-ISCO) crosswalk to connect the 968 SOC occupations to 424 four-digit ISCO occupations and make the measure compatible with European data.…”
Section: Relatedness Complexity and Economic Domain Priorities In Eu Regionsmentioning
confidence: 87%
See 1 more Smart Citation
“…The highest value is observed for physicists and astronomers and the lowest for vehicle cleaners. As Caines, Hoffmann, and Kambourov (2017) show, this variable positively correlates with wage levels and growth, underlining the economic benefits of more complex occupations. We use the 2019 Standard Occupational Classification to International Standard Classification of Occupations (SOC-to-ISCO) crosswalk to connect the 968 SOC occupations to 424 four-digit ISCO occupations and make the measure compatible with European data.…”
Section: Relatedness Complexity and Economic Domain Priorities In Eu Regionsmentioning
confidence: 87%
“…These include the "ability to abstract, solve problems, make decisions, or communicate effectively" (Caines, Hoffmann, and Kambourov 2017, 1). In total, Caines, Hoffmann, and Kambourov (2017) Large values imply that the occupation requires a higher ability to abstract, solve problems, communicate, and make decisions. The highest value is observed for physicists and astronomers and the lowest for vehicle cleaners.…”
Section: Relatedness Complexity and Economic Domain Priorities In Eu Regionsmentioning
confidence: 99%
“…Usually, however, these auxiliary axes do not serve a well-defined purpose. Only Caines et al (2017) formulate a theory of task complexity in relation to routine-intensity and technological change. In most other analyses, the auxiliary task dimension does not add much of substantive interest.…”
Section: Hypothesis 23: Existing Approaches Do Not Account For Differences Between Countriesmentioning
confidence: 99%
“…Several studies suggest that methods used to analyse polarisation patterns need further refinement. For example, Caines et al (2017) introduce a measure of task complexity and demonstrate that, based on this measure, routine intensity does not significantly predict wages and wage growth. Furthermore, Salvatori (2018) shows that the changing the skill mix acts as an important driver for occupational polarisation in the UK.…”
Section: Related Literaturementioning
confidence: 99%
“…However, several research groups recently indicated that these studies need refinement (e.g. Alabdulkareem et al 2018;Caines et al 2017;Salvatori 2018), noting that the traditional occupation-based approaches may neglect the relevance of specific skills and skill bundles, which can potentially be used to explain patterns of labour market polarisation. This aspect is also highlighted by Deming and Kahn (2018) who use vacancy data and exploit the detailed job descriptions to demonstrate that the demand for skills is heterogeneous within occupations, industries and across geographic locations.…”
Section: Introductionmentioning
confidence: 99%